A democracia em Norberto Bobbio - Silva Filho, João Antonio da (2013)
Whenever one mentions the word democracy, it is common that this is associated with the experience of the ancient greeks, whose elaborations passed into history as a synthesis of this form of government. Since then, the supremacy of the democratic system is exalted and presented as the most advanced - under any conditions - even in political regimes with little or no popular participation. Even governments listed in the category of dictatorships guarantee rule under the aegis of "popular participation", one of the assumptions contained in the etymology of the term itself democracy. Be a democrat in these days, so it would be the clearest way of saying that someone is adamant defender of popular control over the state. This paper investigates the origins of democracy, is a historical tour through the universe greek, weaves connections between this experience and others lived in later times until nowadays to propose philosophical reflections on the future of democracy and its variables in the political world. The completion of the object under study in this research is straightforward: humanity sought, met and experienced many political experiences from the greek polis, but democracy was the best contributed to the politicization of society - something that took the italian philosopher Norberto Bobbio to classify as the form of government whose "natural state is to be in transformation." Among others, this was the motivation of the use of the work of Bobbio as a central reference for this work. After all, democracy building is a task that was only initiated by the greeks and passes along the human existence, as something to be built in the likeness of each society